Response of Egg Number to Selection in Rhode Island Chickens Selected for Part Period Egg Production - Nwagu, B.I.; Olorunju, S.A.S.; Oni, O.O.; Eduvie, L.O.; Adeyinka, I.A.; Sekoni, A.A.; Abeke, F.O. (International Journal of Poultry Science, 2006)
Records obtained from 4336 pullets progeny for strain A and 4843 pullets, progeny for strain B under selection for part-period egg production to 280 days of age were used for this study. The response variables measured were Age at sexual maturity (ASM), Egg number to 280 days (EGG280 D), Egg weight average (EWTAV) and Body weight at 40 weeks of age (BWT40). The genotypic response was only 0.42 eggs per generation in the male line. The female line population showed a much higher positive response to selection, the phenotypic value being 1.67 eggs per generation while the genotypic response was 3.1 eggs per generation. The genetic correlation estimates between the different economic traits ranged from -0.70± 0.38 to 0.82 ± 0.42 vs -0.71 ± 0.47 to 0.76 ± 0.29 for the male and female lines respectively. The correlation between egg number and egg weight was small non significant. ASM was highly and negatively correlated with egg production to 280 days in both lines being higher than- 0.60 in most cases. The genetic correlation between egg number and BWT40 showed no definite trend. In the female line, correlated response in age ASM and BWT40 had negative values. In the male line however except for BWT40 which showed a positive correlated response of 3.4g/year, all other traits showed negative correlated responses. Generally it was evident that selection was more effective in improving the egg number in the female line than in the male line showing an increase of 1.67 vs 0.19 eggs per year in the female and male lines, respectively. The low egg number reported was as a result of the delay in sexual maturity especially during the later years of the selection experiment. Another factor that may have contributed to the variable response achieved from generation to generation may also be due to varying season of hatching across generation. However the positive response in the female line population may be attributed to reduced age at sexual maturity.